Pengaruh Penambahan Ekstrak Jeruk Purut (Cytrus hitrix D.C) Sebagai Koagulan Alami Terhadap Karakteristik Karet - Wika Atro Auriyani; Feerzet Achmad; Deviany Deviany; Muhammad Ikhwan Ardian; Rizky Dimas Prasetyo; Aldillah Herlambang; Musa Musa (Politeknik ATI Padang, 2023)
Natural rubber is a plantation commodity that has a significant role in the country's economy. This study aims to determine the effect of the natural coagulant extract of kaffir lime with centrifugation and non-centrifugation treatment on the coagulation process, pH and coagulation time, characteristics of rubber clone IRR 118 and comparison of the quality of rubber with 2% formic acid chemical coagulant. The volume of coagulant used was 75 mL mixed with 150 mL of latex, so that coagulation occurred and produced coagulum. Then the resulting coagulum is analyzed for the characteristics of the rubber to determine the quality of the rubber. Characteristic analysis carried out was Dry Rubber Content (DRC), Initial Plasticity (Po), Plasticity Retention Index (PRI), Mooney Viscosity, ash content, impurities content, volatile matter content, and nitrogen content. The results showed that the natural coagulant extract of kaffir lime could coagulate latex, lowering the pH of latex thereby speeding up coagulation time. From the rubber characteristic test using kaffir lime natural coagulant it complies with SNI 06-1903-2017 SIR 20. The quality of rubber produced from using kaffir lime natural coagulant extract as a coagulant can equate the quality of rubber produced by using 2% formic acid chemical coagulant, but coagulant The natural ingredients used have drawbacks, namely the availability of seasonal fruit, and the need for treatment before being used as a coagulant.